To determine whether the statement is true or false, we first need to solve the equation \(3x^2 - 4x - 4 = 3\).
- Rearranging the equation:
\(3x^2 - 4x - 4 - 3 = 0\)
\(3x^2 - 4x - 7 = 0\).
Next, we will check if -1 and 73 are solutions by substituting these values into the equation \(3x^2 - 4x - 7 = 0\).
Checking -1: \[ 3(-1)^2 - 4(-1) - 7 = 3(1) + 4 - 7 = 3 + 4 - 7 = 0. \] So, -1 is indeed a solution.
Checking 73:
\[
3(73)^2 - 4(73) - 7.
\]
Calculating each term:
\(3(73^2) = 3(5329) = 15987\),
\(-4(73) = -292\),
and then summing:
\[
15987 - 292 - 7 = 15987 - 299 = 15688 \neq 0.
\]
So, 73 is not a solution.
Based on this:
- The statement "The values -1 and 73 are both solutions to the quadratic equation" is False.
For question 2, since the original statement was false because only -1 is a solution, the correct response would be:
Only -1 is a solution to \(3x^2 - 4x - 4 = 3\).